1993
DOI: 10.1023/a:1018937416447
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The in vitro permeabilities of Caco-2 monolayers and permeabilities in tissue sections from colon of monkey, rabbit, and dog were compared using a series of compounds. The selected compounds differed in their physicochemical properties, such as octanol/water partition coefficient, water solubility, and molecular weight. Their structure included steroids, carboxylic acids, xanthins, alcohols, and polyethylene glycols. A linear permeability relationship was established between Caco-2 and colon tissue from both r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(49 citation statements)
references
References 26 publications
5
44
0
Order By: Relevance
“…The absorptive P app were estimated to be 7.15, 6.39, 10.03 9 10 -6 cm s -1 , respectively, for different concentrations, which were well below the suggested threshold value (1.0 9 10 -5 cm s -1 ) for poorly absorbed compounds (Rubas et al 1993) and consistent with the low oral bioavailability of phillyrin observed in pharmacokinetic experiments. In contrast to absorptive transport, the secretory transport appeared to be concentration-dependent suggesting the involvement of a transporter or multiple transporters.…”
Section: Discussionsupporting
confidence: 72%
“…The absorptive P app were estimated to be 7.15, 6.39, 10.03 9 10 -6 cm s -1 , respectively, for different concentrations, which were well below the suggested threshold value (1.0 9 10 -5 cm s -1 ) for poorly absorbed compounds (Rubas et al 1993) and consistent with the low oral bioavailability of phillyrin observed in pharmacokinetic experiments. In contrast to absorptive transport, the secretory transport appeared to be concentration-dependent suggesting the involvement of a transporter or multiple transporters.…”
Section: Discussionsupporting
confidence: 72%
“…Despite this, relating P app in this assay for a given compound to its likely in vivo absorption remains a difficult prospect. Several groups [29][30][31][32] have reported very strong individual correlations between P app across Caco-2 monolayers and in vivo absorption across intestinal epithelium in vivo. However, as noted by Artursson and colleagues 33 the correlation between studies is poor.…”
Section: Discussionmentioning
confidence: 99%
“…Active transport is more difficult in that it needs to be evaluated separately for each transporter studied. 189 are about an order of magnitude greater. This is most likely due to the fact that Rubas et al 189 used a system in which the unstirred water layer was reduced while Artursson and Karlsson188 used a stagnant system.…”
Section: In Vztroizn Vzvo Correlationsmentioning
confidence: 92%
“…189 are about an order of magnitude greater. This is most likely due to the fact that Rubas et al 189 used a system in which the unstirred water layer was reduced while Artursson and Karlsson188 used a stagnant system. Completely absorbed drugs in humans had Papp values greater than 1 x 10-6 cm/s and 7 x 10-5 cm/s in Artursson's and Rubas' models, respectively.…”
Section: In Vztroizn Vzvo Correlationsmentioning
confidence: 92%